Pengaruh Konflik Peran dan Ketabahan Terhadap Burnout Akademik Pada Mahasiswa Organisatoris di Fakultas Kedokteran Universitas Udayana - Dyantari, Kadek Ratih; Simarmata, Nicholas (Peneliti.net, 2024)
Organizational students are responsible for undergoing lectures, which are also accompanied by their involvement in organizations on campus. This makes the lecture situation even more challenging. Academically, lectures have made various demands that create a stressful situation for students. Situational factors, namely role conflict, and individual factors, namely grit, are thought to have an influence on academic burnout. The purpose of this study is to determine the effect of role conflict and grit on academic burnout. The measuring instruments used in this study were the academic burnout scale with a reliability of 0.892, the role conflict scale with a reliability of 0.918, and the grit scale with a reliability of 0.889. The sample size in this study was 190 organizational students at the Faculty of Medicine, Udayana University. Data analysis in this study used multiple linear regression techniques with a significance value of 0.000 and a coefficient of determination of 0.437. These results mean that there is a significant effect of role conflict and grit together at 43.7% on academic burnout. Each independent variable has a significant effect on academic burnout, with the beta coefficient of role conflict showing positive results, while the beta coefficient of grit shows negative results. Based on these results, it is important for organizational students to minimize role conflict and develop grit in an effort to reduce academic burnout.